The historical factors behind the migration of Guimbalanons to the island of Guimaras since 1950s - Claveria, Cherry Araquil (2002.)
This is a descriptive study of the historical factors behind the migration of Guimbalanons to the island of Guimaras. Data was gathered in a form of questionnaires and a one-on-one interview with the 25 respondents randomly selected from the (3) barangays within the Municipality of Jordan namely: San Miguel, Sta. Teresa, and Lawi; and one (1) barangay from the municipality of Nueva Valencia, the barangay Poblacion. Results show that there are push (marriage, family and job changes/loss) and pull (land expansion, space/peace and order and properties of relatives) underlying the migration of Guimbalanons to the island of Guimaras. Changes in status and family ties are affected by the adjustment process in their place of destination. Migration affects both the place of origin (Guimbal) and the place of destination (Guimaras) in relation to the availability of amenities and population growth. This study concludes that there are historical factors behind the migration of Guimbalanons to the island of Guimaras.
Research Proposal (Undergraduate, Bachelor of Arts in Political Sciences) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Guimbalanons